Communism and Labor Unions: The Changing Perspectives of Mennonites in Canada and the United States - Thiessen, Janis Lee (Direction, 2009)
Mennonite political theology, at least as manifested by church pronouncements on communism and labor unions, has been both more and less progressive than the ideology of the broader North American society. When the United States and Canadian governments were obsessed with tracking down enemy “reds” within, Mennonites passed resolutions that cautioned against the identification of Christianity with anti-communism. However, while the Second World War and the decade immediately following saw the expansion of labor unions as North Americans flocked to join them, Mennonites issued statements warning against the compromise of Christian principles that union membership would entail. –Introduction
https://winnspace.uwinnipeg.ca/handle/10680/1650